2018
DOI: 10.1007/s10265-018-1025-x
|View full text |Cite
|
Sign up to set email alerts
|

Spiral phyllotaxis underlies constrained variation in Anemone (Ranunculaceae) tepal arrangement

Abstract: Stabilization and variation of floral structures are indispensable for plant reproduction and evolution; however, the developmental mechanism regulating their structural robustness is largely unknown. To investigate this mechanism, we examined positional arrangement (aestivation) of excessively produced perianth organs (tepals) of six- and seven-tepaled (lobed) flowers in six Anemone species (Ranunculaceae). We found that the tepal arrangement that occurred in nature varied intraspecifically between spiral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In line with a previous report (Kitazawa and Fujimoto, 2018), we confirmed that the aestivations of 5-to 7-lobed flowers were constrained to several types including the trimerous double-whorl and the spirals, despite considerable intraspecific variation of tepal numbers in Anemone species ( Supplementary Table 2) (Yule, 1902;Fujimoto, 2014, 2016a), even when there was a two-fold increase in the sample size ( Figures 2B-D, Supplementary Table 1). Therefore, we explored the constrained coexistence of whorled and spiral flowers in populations with more than 7 and <5 tepals, in four Anemone and one Eranthis species (sections Positional Arrangement of Perianth Organs and Plant Samples).…”
Section: Constrained Coexistence Of Whorled and Spiral Flowers In Popsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with a previous report (Kitazawa and Fujimoto, 2018), we confirmed that the aestivations of 5-to 7-lobed flowers were constrained to several types including the trimerous double-whorl and the spirals, despite considerable intraspecific variation of tepal numbers in Anemone species ( Supplementary Table 2) (Yule, 1902;Fujimoto, 2014, 2016a), even when there was a two-fold increase in the sample size ( Figures 2B-D, Supplementary Table 1). Therefore, we explored the constrained coexistence of whorled and spiral flowers in populations with more than 7 and <5 tepals, in four Anemone and one Eranthis species (sections Positional Arrangement of Perianth Organs and Plant Samples).…”
Section: Constrained Coexistence Of Whorled and Spiral Flowers In Popsupporting
confidence: 91%
“…× hybrida W, and A. hepatica, and second for A. × hybrida PP and E. pinnatifida (EAIEIA and EAIAEI ranked first, respectively, for the last two species; Figure 2C), in line with the results of a previous report (Kitazawa and Fujimoto, 2018). In addition, in several populations, the 6-tepaled aestivation exhibited a reproducible difference from the above-mentioned average of total populations.…”
Section: Species-and Population-specificity Of the Constrained Aestivsupporting
confidence: 90%
“…Another character is the order of organ initiation. A third character (Kitazawa and Fujimoto, 2018;Fujimoto and Kitazawa, 2020) is the pattern of overlapping between margins of adjacent organs (aestivation). Quincuncial aestivation normally correlates with sequential sepal initiation in angiosperms.…”
Section: Resultsmentioning
confidence: 99%
“…Smith et al assumed in their mathematical model that the inhibitory power of each primordium decays exponentially with age and stated that this decay promoted phyllotactic pattern formation de novo, as well as pattern transition, and allowed the maintenance of patterns for wider ranges of parameters [9]. A DC1-based model equipped with a primordial age-dependent change in the inhibitory power was also used to investigate floral organ arrangement [35, 36]. In these studies, however, temporal changes in the inhibitory power were examined under limited ranges of parameters focusing on particular aspects of phyllotactic patterning, and the possibility of the generation of minor patterns, such as orixate phyllotaxis, was not addressed.…”
Section: Discussionmentioning
confidence: 99%